TECHNIQUES AND APPROACHES FOR INCREASING LANGUAGE LEARNERS’S VOCABULARY AT NON- PHILOLOGICAL UNIVERSITIES (American Journal of Pedagogical and Educational Research, 2023)
Due to the emphasis that is frequently placed on the definitions of new terms, both in books and in classroom settings, vocabulary development is a crucial component of learning a foreign language. Additionally, it is crucial to language learning and at the heart of language education. Recent research indicates that teaching vocabulary may be problematic because many teachers are not confident about best practice in vocabulary teaching and at times don’t know where to begin to form an instructional emphasis on word learning (Berne & Blachowicz, 2008).